Study of sociodemographic profile, maternal, fetal outcome in preeclamptic and eclamptic women: a prospective study - ., Vedavathi; Sood, Rajeev (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Preeclampsia is pregnancy specific disease, lead to maternal, perinatal morbidity and mortality. This study is conducted to identify the socio demographic profile of subjects suffering from preeclampsia and its effect on maternal and fetal health. Methods: This prospective study was conducted at department of obstetrics and gynecology, Kamla Nehru State Hospital, Shimla, in this, 100 preeclamptic women were included. Preeclampsia was diagnosed with blood pressure of ≥140/90 mmHg noted for the first-time during pregnancy, after 20 wks of gestation and proteinuria. Demographic details were collected. Investigations i.e. hemogram, liver and renal function tests, coagulation profile and fundoscopy were done. Maternal and perinatal outcomes were recorded. Results: In this study, majority of the subjects were primigravida 65. In this, 11 subjects had systolic blood pressure of 140-159 mmHg and 89 subjects had systolic blood pressure of > 160 mmHg. 25 subjects had diastolic blood pressure of 90-109 mmHg and 75 subjects had diastolic blood pressure of > 110 mmHg. In this, 82 subjects had warning symptoms, mainly headache 49. 14 subjects showed hypertensive changes in fundus. Unfavorable Bishop Score, observed in 86 subjects and 78 subjects were induced after controlling blood pressure. Majority of subjects had vaginal delivery 73. Majority of the subjects had deranged liver function 61. Maternal morbidity was reported in 54 subjects. Intrauterine death reported in 14 subjects. Birth weight was < 2.5 kg was observed in 70 babies. Out of 74 live births, 53 neonates required admission in NICU and 16 neonates died in NICU. Conclusions: It may be concluded that, maternal and neonatal morbidity and mortality can be reduced by early identification of risk factors and timely intervention is the hall mark in preventing the maternal and perinatal morbidity and mortality.